Role of Long Non-Coding RNAs in Conferring Resistance in Tumors of the Nervous System - Ghafouri-Fard, Soudeh; Agabalazadeh, Amin; Abak, Atefe; Shoorei, Hamed; Hassanzadeh Taheri, Mohammad Mehdi; Taheri, Mohammad; Sharifi, Guive (Frontiers in Oncology, 2021)
Tumors of the nervous system can be originated from several locations. They mostly have high mortality and morbidity rate. The emergence of resistance to chemotherapeutic agents is a hurdle in the treatment of patients. Long non-coding RNAs (lncRNAs) have been shown to influence the response of glioblastoma/glioma and neuroblastoma to chemotherapeutic agents. MALAT1, NEAT1, and H19 are among lncRNAs that affect the response of glioma/glioblastoma to chemotherapy. As well as that, NORAD, SNHG7, and SNHG16 have been shown to be involved in conferring this phenotype in neuroblastoma. Prior identification of expression amounts of certain lncRNAs would help in the better design of therapeutic regimens. In the current manuscript, we summarize the impact of lncRNAs on chemoresistance in glioma/ glioblastoma and neuroblastoma.